PEMBERDAYAAN MASYARAKAT DALAM PENGGUNAAN DANA HIBAH DI KELURAHAN SUMBERSARI TAHUN 2011 UNTUK PEMBANGUNAN WILAYAH KOTA MALANG - Dewi Citra Larasati (REFORMASI, 2013)
Rural-Oriented Grant Fund Program extends the grant fund to the community through rural community empowerment agency. This program is released by the government of Malang City to improve community participation through empowerment strategy. This program is initiated from planning, implementation, throughout accountability. In essence, Grant Fund Program is coming from, managed by, and given for the community. Sumbersari Village is exception, however. Low participation of community in the Grant Fund Program is estimated.